The effect of interprofessional education on interprofessional professionalism behaviors of the surgical team members - Azam Hosseinpour; Fatemeh Keshmiri; Sara Jambarsang; Fatemeh Jabinian; Seyed Mostafa Shiryazdi (BMC, 2022)
Abstract Introduction Interprofessional professionalism (IPP) has been introduced as one of the critical sub-competencies of interprofessional collaboration. This study aimed to assess the effect of interprofessional education on the behavior of interprofessional professionalism among the surgical team in the intervention compared to the control group. Methods This is a quasi-experimental study. The participants were nurses in anesthetist and surgical technology and surgical residents of Shahid Sadoughi Hospital (n = 150) who were included in the study by the census. The intervention employed an interprofessional case-based learning strategy to explore themes of interprofessional professionalism. Two assessors used the Interprofessional Professionalism Assessment (IPA) tool to measure learners' performance while observing them in practice prior to the intervention, one and three months after the intervention. Data were analyzed using descriptive tests (mean and SD) and RM-ANOVA. Results In this study, the participants in the intervention (n = 78) and the control (n = 72) groups entered the study. The Baseline IPA scores of participants were reported as 1.25 (0.12) and 1.21 (0.1) in the intervention and control groups, respectively. The IPA score of the participants in the intervention group (2.59 (0.26) and 2.54 (0.24)) was higher than the control group (1.17 (0.08) and 1.12 (0.07)) after one and three months of the intervention (P = 0.0001). The effect of educational interventions was reported at the large level (Eta Square = 0.89). Conclusion Interprofessional professionalism in surgical teams has been recognized as a critical element of team-based care. The present study used an interprofessional education strategy to develop IPP behavior. All professions benefited from interprofessional education. It is suggested that all surgical team professionals participate in interprofessional education.